Perbaikan Produktivitas UMKM Melalui Pemilihan Mesin Jahit Yang Tepat: Studi Kasus Pengrajin Sulam Usus - Sundari, Susanti; Amir, Aprilianto; Suryani, Suryani (Fakultas Teknik Universitas Tulang Bawang, 2024)
House Tapis Citra (HTC), which produces the typical Lampung sulam usus, faces a problem the form of a sewing machine used has low productivity, only capable of producing 4 meters of product per day, while using a high-speed machine can produce 12 meters per day according to the specifications. The high demand from consumers cannot always be met. If urgent orders are required, they must be ordered from others which will increase production costs by 50%. The purpose of this research is to clearly identify the root causes of low productivity at HTC by analyzing through a fishbone diagram. After the main factors are identified, improvements are made and their effectiveness is measured. With the case study research method using a fishbone analysis tool, it will be able to answer research questions, and the resulting strategies can be made recommendations for further improvement solutions. The research results show that HTC employees' ability to produce output using a new machine is 0.85 meters/hour, while the old machine is only 0.5 meters/hour. The employees' ability to produce output at this time with the new machine is still 57%, and can still be improved to reach the remaining 43% by being given training to produce 12 meters/day to the machine spec. The souvenir production process produces 200 pieces/day with a work productivity of 25 pieces/hour for new machine, while the old machine only produces 100 pieces/day with productivity of 13 pieces/hour. Innovation and technology are able to increase the productivity of HTC. Keywords: Fishbone, HTC, MSMEs, Machine, Productivity, Sulam usus